The Effect of Cooperative Learning Model Course Review Horay Contains Science Literacy on Learning Competencies Students - Utari Adeviani; Ardi Ardi; Resti Fefria; Syamsurizal Syamsurizal (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The Research problems at SMAN 2 Lubuk Sikaping are students having difficulty in formulating problems, analyzing and finding solutions to difficulties in the learning process, leadership and motivation, level of activity and student learning in the learning process is still low and learning models that are rarely used and are still centered on the teachers. Efforts that can be done are implementing the learning model course review containing science literacy at SMAN 2 Lubuk Sikaping. The purpose of this study was to study the improvement of knowledge competencies, attitudes and skills of students through a horay review course model with scientific literacy at SMAN 2 Lubuk Sikaping. This type of research is a quasi-experimental study with a posttest randomized design control group design. The study population was all class X SMAN 2 Lubuk Sikaping registered in the 2018/2019 school year controlling three classes. Sampling using purposive sampling technique. The research hypothesis evaluates using the t-test. Conclusions of the study about the application of the learning model course review horay with science literasy the learning competenci of knowledge, attitudes, skills of class X students of SMAN 2 Lubuk Sikaping